2017
DOI: 10.1371/journal.ppat.1006763
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans FRE8 encodes a member of the NADPH oxidase family that produces a burst of ROS during fungal morphogenesis

Abstract: Until recently, NADPH oxidase (NOX) enzymes were thought to be a property of multicellularity, where the reactive oxygen species (ROS) produced by NOX acts in signaling processes or in attacking invading microbes through oxidative damage. We demonstrate here that the unicellular yeast and opportunistic fungal pathogen Candida albicans is capable of a ROS burst using a member of the NOX enzyme family, which we identify as Fre8. C. albicans can exist in either a unicellular yeast-like budding form or as filament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 73 publications
7
64
0
Order By: Relevance
“…Notably, tetraploid cells grown on PRE-SPO medium exhibited the strongest signal, with 2.0-fold higher fluorescence levels than diploid cells on this medium ( Fig 4B). Previous work showed that C. albicans also produces ROS during hyphal morphogenesis (Rossi et al, 2017). Consistent with this finding, cells grown on YPD medium at 37°C, a growth condition which induces filamentation, stained positively with CellROX Green ( Fig EV3A).…”
Section: Candida Albicans Cells Experience Elevated Oxidative Stress supporting
confidence: 86%
See 1 more Smart Citation
“…Notably, tetraploid cells grown on PRE-SPO medium exhibited the strongest signal, with 2.0-fold higher fluorescence levels than diploid cells on this medium ( Fig 4B). Previous work showed that C. albicans also produces ROS during hyphal morphogenesis (Rossi et al, 2017). Consistent with this finding, cells grown on YPD medium at 37°C, a growth condition which induces filamentation, stained positively with CellROX Green ( Fig EV3A).…”
Section: Candida Albicans Cells Experience Elevated Oxidative Stress supporting
confidence: 86%
“…Previous work showed that C. albicans also produces ROS during hyphal morphogenesis (Rossi et al , ). Consistent with this finding, cells grown on YPD medium at 37°C, a growth condition which induces filamentation, stained positively with CellROX Green (Fig EV3A).…”
Section: Resultsmentioning
confidence: 99%
“…However, we recently found that Cu-only SOD5 from unicellular C. albicans can act in signaling involving ROS and a fungal NOX enzyme known as FRE8 (78). C. albicans FRE8 and SOD5 together generate H 2 O 2 that can help drive morphogenesis of the fungus into an invasive filamentous state (78).…”
Section: The Role Of Cu-only Sods In Fungal Pathogenesis and Signalingmentioning
confidence: 99%
“…Recent studies have shown that C. albicans produces a burst of extracellular O 2 ·− by a fungal NOX enzyme (FRE8) during morphogenesis and that this O 2 ·− serves as a substrate for extracellular Cu-only SOD5. The diffusible H 2 O 2 product generated by SOD5 then acts as a signal to modulate morphogenesis through a mechanism that is currently not known 146 . In fact, SOD5 is specifically induced during the fungal oxidative burst, indicating that SOD5 may have evolved to deal with fungal-derived ROS 138 .…”
Section: Fungal Pathogensmentioning
confidence: 99%